Percutaneous or mini-invasive surgical radiofrequency re-ablation of atrial fibrillation: Impact on atrial function and echocardiographic predictors of short and long-term success - Montserrat, Sílvia; Gabrielli, Luigi; Borràs, Roger; Cascos, Enric; Castellá, Manel; Sanchis, Laura; Bijnens, Bart; Mont, Lluís; Sitges, Marta (Frontiers in Cardiovascular Medicine, 2022)
Objectives: The aim of this study was to compare percutaneous catheter ablation versus minimally invasive surgical ablation, evaluating the impact of repeated ablation on atrial function and evaluating predictors of atrial fibrillation (AF) recurrence. Background: When AF ablation fails, re-ablations are required in up to 40% of patients to treat recurrent arrhythmia; surgical ablation is more effective than catheter ablation. Methods: Thirty-two patients with failed prior catheter ablation and referred for a second ablation (18 catheter and 14 surgical) were prospectively randomized included. Left atrial volumes, strain, and strain rate were measured with 2D speckle tracking echocardiography at baseline and 6 months after the procedures to assess left atrial functions. Patients received up to 1 year of clinical and Holter follow-up. Results: At the 12-month follow-up, catheter ablation was effective in 56% and surgical ablation in 72% of patients (OR 2 (CI 0.45-8.84), p 0.36). Left atrial booster function was similar in all patients, but left atrial reservoir function was more impaired in those patients who underwent surgical ablation. Left atrial booster function was predictive of arrhythmia recurrence after both catheter and surgical ablation: late diastolic strain rate (LASRa) cut-off ≤-0.89 s-1 (sensitivity 88%, specificity 70%, AUC 0.82) and ≤ -0.85 s-1 (sensitivity 60%, specificity 100%, AUC 0.82), respectively. Conclusion: Surgical ablation has a more negative impact on LA reservoir function despite being slightly more effective in arrhythmia suppression. LA booster function is not significantly impaired by either procedure. LA booster function predicts arrhythmia elimination after a re-ablation (catheter or surgical).